Efektivitas Edukasi Video Terhadap Pengetahuan Dan Perilaku Pencegahan Penyakit IMS Remaja Madrasah Aliyah Muhammadiyah Kota Gorontalo - Karsum Violeta Kadir; Irwan; Suardi (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Sexually Transmitted Infections (STIs) remain a global health problem, including among adolescents who are vulnerable due to limited knowledge about STIs and suboptimal preventive behavior. Globally, STIs contribute to approximately 2.3 million deaths. In Indonesia, the number of new STI cases has reached 45,000 cases. In Gorontalo City, STI cases among adolescents increased from 370 cases in 2023 to 515 cases in 2024. Video-based education is considered effective because it delivers information through audiovisual media, making it easier for adolescents to understand. This study aims to determine the effectiveness of video-based education on adolescents' knowledge and preventive behavior regarding STIs at Madrasah Aliyah Muhammadiyah Kota Gorontalo.This quantitative pre-experimental study used a one-group pretest-posttest design with 31 twelfth-grade students selected via total sampling. Knowledge and behavior questionnaires were used as research instruments. The collected data were analyzed using the Wilcoxon signed-rank test because the data were not normally distributed.The results showed that the average knowledge score increased from 8.52 to 11.46, while the behavior score increased from 32.55 to 38.94. The p-values for knowledge and behavior were both 0.000 (p<0.05). In conclusion, video-based education had a significant effect on adolescents' knowledge and preventive behavior regarding STIs. It is recommended that video-based education be combined with discussions to further enhance adolescents' understanding.